A Note on Elizabeth Isabella Spence and her Sketches of the Present Manners, Customs, and Scenery of Scotland (1811). Issue 2 (September 2021) - Carruthers, Gerard; Thomas Gallagher, Kevin
Abstract : This article discusses several engagements with Burns and Robert Fergusson by Elizabeth Isbaella Spence in the early nineteenth century, as well the textual variance found in several nineteenth-century versions of Burns's 'Epistle to Rob t Graham, Esq: of Fintry on the Election for the Dumfries string of Boroughs, Anno 1790' (1790). Spence is involved in the contemporary Romantic conceptualisation of Scotland, and she visited Burns's widow Jean Armour in Dumfries as part of a tour of the country providing an account of her encounter. This note examines a particular textual variant which appears in Spence's publication of Burns's 'Epistle to Graham of Fintray', tracing this variant throughout several key early-to-mid nineteenth-century versions.